Educational technology 1 - Corpuz, Brenda B.; Lucido, Paz I. (Cubao, Philippines : Lorimar Publishing Company Inc., 2012)
This second edition of this book on Educational Technology 1 is aligned with the National Competency- Based Teacher Standards (NCBTS), the standard of good teaching in the Philippines consisting of seven (7) integrated domains, twenty-one (21) strands and eighty (80) performance indicators with the end in view in contributing to the formation of competent and committed professional teachers. It is focused on the development of the 21st century teachers who can respond to the demands of the K to 12 Basic Education Curriculum which the Department of Education began implementing in SY 2012- 2013. It is dotted with activities which are in keeping with the trends in education such as reflective, integrative, interactive, inquiry-based, brain-based and research-based teaching, constructivism multiple intelligences, multicultural education, and authentic assessment. Likewise, this edition updates the readers on educational legislations including the universalization of Kindergarten.
Foreword iii -- Acknowledgement iv -- Letter to the Teacher v -- Letter to the student ix -- Meaning of Educational Technology 13 -- Technology: Boon or Bane? 21 -- The Roles of Educational Technology in Learning 29 -- Systematic Approach to Teaching 36 -- The Cone of Experience 44 -- Using and Evaluating Instructional Materials 55 -- Direct Purposeful Experiences 62 -- Teaching with Contrived Experiences 70 -- Teaching with Dramatized Experiences 80 -- Demonstration in Teaching 89 -- Making the Most of Community Resources and Field Trips 96 -- The Power of Film, Video and TV in the Classroom 104 -- Teaching with the Visual Symbols 112 -- Maximizing the Use of the Overhead Projector and the Chalkboard 137 -- Project- Based Learning and Multimedia: What It Is? 149 -- Using the Project- Based Learning Multimedia as a Teaching- Learning Strategy 159 -- Assessment in a Constructivist, Technology- Supported Learning 172 -- Roles and Function of an Educational Media Centre 182 -- References 193 -- Afterword 196
Keywords: EDUCATIONAL TECHNOLOGY -- PHILIPPINES